Competitive Advantage of SDITQ Bakkah Martapura Through an Islamic Education-Based Learning Strategy - Nugroho Widi Susanto; Dina Hermina (Journal of Elementary Education Research and Practice, 2025)
The Industrial Revolution 4.0 presents significant challenges to educational institutions in Indonesia, including Islamic-based schools like SDITQ Bakkah Martapura, compelling them to enhance their competitiveness by delivering high-quality education. A qualitative study aims to explore implementing Islamic-based education that integrates academic excellence with moral values to address the challenges posed by globalization effectively. Data were collected from 22 informants through interviews, observations, and document analysis to understand the factors influencing the quality of education within this framework. The results indicate that the tahfizhul Qur'an program, an integrated religious curriculum, and a supportive Islamic learning environment significantly contribute to the school's competitive advantage. The tahfizhul Qur'an program enhances students' Arabic language skills and fosters their discipline and character development. Furthermore, a comprehensive religious curriculum deepens students' understanding of Islamic values, while a nurturing school environment supports their character growth. This research recommends innovative strategies and collaboration among the school, parents, and the community to improve the quality of education at SDITQ Bakkah Martapura continuously